Corpo de Dança do Amazonas : história e memória - Lima, Getúlio Henrique Rocha (2013)
This research aimed to investigate the history and memory of the Body Dance Amazon. This dance company was created by the Government of the State of Amazonas through the Secretary of State for Culture, in 1998, on the initiative of Amazonino Mendes, governor at the time, and the Secretary of State for Culture, Robério Braga. To develop this study we worked with oral history, where 9 employees participated in the interviews. They are the current artistic director, two teachers, three former dancers, one dancer and two collaborators who accompanied the planning and execution of the project to create the group. The creation of the group was seen as a political initiative and also as a result of the artistic movement in dance before. Its history and its educational activities, artistic and social were presented from the three phases of artistic directions. Keywords: history, oral history, dance.